Alterations of the White Matter in Patients With Knee Osteoarthritis: A Diffusion Tensor Imaging Study With Tract-Based Spatial Statistics - Cheng, Shirui; Dong, Xiaohui; Zhou, Jun; Tang, Chenjian; He, Wenhua; Chen, Yang; Zhang, Xinyue; Ma, Peihong; Yin, Tao; Hu, Yimei; Zeng, Fang; Li, Zhengjie; et al. (Frontiers in Neurology, 2022)
Background: Gray matter alterations and functional abnormalities have been observed in patients with knee osteoarthritis (KOA). However, very little is known about white matter changes. We evaluated the fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) to investigate the alterated white matter in KOA knee pain patients. Methods: One hundred-sixty-six patients with KOA and 88 age- and gender-matched healthy controls had been recruited and underwent brain MRI acquisition in this study. The diffusion tensor imaging (DTI) data were analyzed using tract-based spatial statistics (TBSS). Statistical significance was determined at p < 0.05, corrected by using threshold-free cluster enhancement (TFCE) method. The potential correlations between FA, MD, AD, RD values and disease duration, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, visual analogue scale (VAS) scores were also performed. Results: The FA values of the body of corpus callosum, splenium of corpus callosum, bilateral superior longitudinal fasciculus, cingulum, bilateral superior corona radiata, right posterior corona radiata were increased in patients with KOA compared with healthy controls (p < 0.05, TFCE corrected). Significant decreased MD, AD and RD values of the genu of corpus callosum, body of corpus callosum, splenium of corpus callosum, corona radiata, right posterior thalamic radiation, superior longitudinal fasciculus, middle cerebellar peduncle were also found in KOA knee pain patients (p < 0.05, TFCE corrected). Negative correlations were found between WOMAC scores and AD values of body of corpus callosum, splenium of corpus callosum (p < 0.05, FDR corrected). Conclusion: This study showed global white matter alterations in KOA knee pain patients comparing with healthy controls. The sensorimotor and pain-related white matter alteration might be involved in the development of KOA and reflect a set of maladaptive plastic changes.